In cellulo structure determination of a novel cypovirus polyhedrin. - Axford, D; Ji, X; Stuart, D; Sutton, G (2014)
This work demonstrates that with the use of a microfocus synchrotron beam the structure of a novel viral polyhedrin could be successfully determined from microcrystals within cells, removing the preparatory step of sample isolation and maintaining a favourable biological environment. The data obtained are of high quality, comparable to that obtained from isolated crystals, and enabled a facile structure determination. A small but significant difference is observed between the unit-cell parameters and the mosaic spread of in cellulo and isolated crystals, suggesting that even these robust crystals are adversely affected by removal from the cell.